Optimization of cultural growth parameters of Mycogone perniciosa under lab conditions - Sabharwal, Aprna; Kapoor, S (Mushroom Research, 2013)
Agaricus bisporus (Lange) Imbach, the button mushroom is the most commonly cultivated mushroom worldwide. Mycogone perniciosa (Magnus) is the causal organism of wet bubble disease also known as La Molé of A. bisporus (Lange) Imbach. The disease is very contagious and results in severe crop loss. In the present study the effect of external factors like medium type, pH and temperature of medium on the growth of Mycogone perniciosa was studied. Mycopathogen strains were isolated from diseased mushroom obtained from Dehriwal (MPD), Wingerwal (MPW) and Nabha (MPN) regions of Punjab and used against one reference strain of the pathogen collected from Department of Microbiology, Punjab Agricultural University, Ludhiana. The optimal conditions for growth and storage of mycopathogen were studied. Both malt extract and potato dextrose media supported the mycelial growth in liquid and solid state. However, the use of malt extract was not superior to that of potato dextrose medium on long term basis. The optimal culture conditions in liquid and solid state were pH ranging between 6.8-7.5 and temperature of 25°C. The mycelial growth of fungi (in gms.) in liquid state and (in cm) in solid state were observed within pH range of 5.5 to 7.5 and temperature range 15°C to 30°C. Further studies on mycopathogen both in vitro and in vivo for control of the mycopathogen and yield loss of white button mushroom are currently being assessed.